A Route Towards Sustainability Through Engineered Polymeric Interfaces. Issue 4 (30th May 2014) - Reeja‐Jayan, B.; Kovacik, Peter; Yang, Rong; Sojoudi, Hossein; Ugur, Asli; Kim, Do Han; Petruczok, Christy D.; Wang, Xiaoxue; Liu, Andong; Gleason, Karen K.
<x xml:space="preserve">Abstract</x> Chemical vapor deposition (CVD) of polymer films represent the marriage of two of the most important technological innovations of the modern age. CVD as a mature technology for growing inorganic thin films is already a workhorse technology of the microfabrication industry and easily scalable from bench to plant. The low cost, mechanical flexibility, and varied functionality offered by polymer thin films make them attractive for both macro and micro scale applications. This review article focuses on two energy and resource efficient CVD polymerization methods, initiated Chemical Vapor Deposition (iCVD) and oxidative Chemical Vapor Deposition (oCVD). These solvent‐free, substrate independent techniques engineer multi‐scale, multi‐functional and conformal polymer thin film surfaces and interfaces for applications that can address the main sustainability challenges faced by the world today.